Potential drug incompatibilities in the neonatal intensive care unit: a network analysis approach - Ramon Weyler Leopoldino; Haline Tereza Costa; Tatiana Xavier Costa; Rand Randall Martins; António Gouveia Oliveira (BMC, 2018)
Abstract Background There is little information on the frequency of drug incompatibilities in neonatal intensive care units (NICU) and the agents most commonly involved in them. The objective of the study was to characterize potential Drug Incompatibilities (DI) in the NICU by frequency, type and combination of drugs. Methods Between August 2015 and December 2016, all neonates admitted for more than 24 h and who received any drug treatment were included in this cohort study conducted in the NICU of a teaching maternity hospital in Brazil. Patient data were collected from patient records and prescription orders, and the compatibilities of all drug pairs were classified using the Trissel's™ 2 IV Compatibility tool. Network analysis was performed in order to visualize the drug pairs commonly involved in potential DI. Results The study population consisted of 281 neonates with a median NICU length of stay of 11 days (range 2-184) and received 1343 intravenous medications. A total of 1114 potential DI were identified, 469 (42.1%) were restricted compatibilities, 348 (31.2%) unknown compatibilities and 297 (26.7%) documented incompatibilities. The incidence of documented incompatibilities in the NICU was 25.0% patient-days (95% confidence interval (CI) 19.4-30.7% patient-days). Incompatible potential DI affected 46.3% (95%CI 40.3-52.3%) of the neonates. Ampicillin (408 of 1114 pairs), gentamicin (216 of 1114 pairs) and aminophylline (197 of 1114 pairs) were the main medicines involved in potential DI. Conclusion Potential DI are extremely common in NICU, with half of the population susceptible to simultaneous administration of incompatible medications. More research is needed to understand the actual drug incompatibilities and their clinical outcomes.